(untitled) (Research, Society and Development, 2021)
The Project Ciência em Órbita has been developed by PET/Conexão de Saberes: Física e Popularização da Ciência (Unifei – Campus Itabira) since 2015. This paper depicts a set of Physics experiments performed by the PET team with aim at sharing knowledge in a didatic, dinamic clear and clear way. The experiments explore the concepts of Physics with a practical approach, comprise several different areas such as Basic Physics, Mechanics, Thermodynamics, Electricity and Optics and include Plasma Globe, Giant Soup Bubble, Van de Graaff Generator, Tesla Coil, and others. Besides, an itinerant Planetarium is also used to present Astronomy in a ludic and fun perspective. The experiments were presented in free, public events, always adapting the language to the age range of the audience. The methodology adopted in this paper is of a case study with qualitative analysis and comprises the development of the project and its main characteristics and contributions for both participants: the audience and the team. Among these contributions, it is worth stressing the benefits of the bond between the Society and the University as a mean to promote knowledge.